Veto or failure? Notes on the Peruvian intelligentsia during the aristocratic Republic - Portocarrero Grados, Ricardo (1997)
The recent appearance of the book by Osmar Gonzales, The failed sanchos, has motivated these lines. It is not a review of the cited book, but, rather, of motivating reflections for its reading and that in this way find a valid interlocutor for a necessary discussion on the study of intellectuals. Except for the work of Salazar Bondy and David Sobrevilla, who sought to provide global and far-reaching visions, most of the research work on intellectuals can be divided into two large groups.